Regulatory Lessons from the Crisis of Costa Rica's Mutual Fund Industry - Carvajal, Ana (IMF Working Papers; Working Paper ;, 2006)
In 2004, the mutual fund industry of Costa Rica experienced a massive run by investors that reduced the industry to half its size in a month. This paper explores how weaknesses in the regulatory framework played a role in the crisis and draws lessons for developing countries. The analysis of events demonstrates the need for developing countries to design a multi-pillar framework for securities regulation as well as to strengthen financial literacy and capacity building. At the micro level it shows the importance of market conduct rules and the challenges that the implementation of mark-to-market poses for developing markets.